DAMPAK HUTAN KEMASYARAKATAN TERHADAP ASPEK SOSIAL EKONOMI MASYARAKAT (STUDI PADA MASYARAKAT PEDULI GAMBUT SUKAMAJU, KPH KAYU TANGI) - Martapani, Ahmad Nopan; Fauzi, Hamdani; Naparin, Muhammad (JURNAL RIMBA LESTARI, 2021)
The purpose of this research was to describe the Community Forest program, and analyze the benefits of Community Forest to the social economic aspects of MPG Suka Maju group members as a IUPHKm. The determination of informants was done deliberately based on the data of members of the group who were still active in the membership which amounts to 19 people. The research approach used in this study was exploratory and descriptive of analytics. Data collection techniques use observation, interview and documentation techniques. HKm had a positive impact on the community both on social and economic aspects. HKm could be a solution for farmers in ensuring their legality in accordance with the government's objectives as a program to improve the welfare of the community. The social impact occurs on HKm MPG SukaMaju farming group was in the form of increasing public knowledge of social forestry that provides community opportunities to manage forests. In addition, it also had the effect of resolving land conflicts, changes in people's behavior in clearing land without burning, and the strengthening of the gotong royong culture that was beginning to fade. The economic impact on MPG SukaMaju farmers group was in the form of increased production, increased revenue, labor absorption, business opportunity development, and business partnerships.